Effect of material selection on tibial post stresses in posterior-stabilized knee prosthesis: a comparison among conventional, cross-linked, and vitamin E-stabilized polyethylene. Issue 11 (2nd November 2020) - Huang, Chang-Hung; Lu, Yung-Chang; Hsu, Lin-I; Liau, Jiann-Jong; Chang, Ting-Kuo; Huang, Chun-Hsiung
Abstract : Aims: The material and design of knee components can have a considerable effect on the contact characteristics of the tibial post. This study aimed to analyze the stress distribution on the tibial post when using different grades of polyethylene for the tibial inserts. In addition, the contact properties of fixed-bearing and mobile-bearing inserts were evaluated. Methods: Three different grades of polyethylene were compared in this study; conventional ultra high molecular weight polyethylene (UHMWPE), highly cross-linked polyethylene (HXLPE), and vitamin E-stabilized polyethylene (VEPE). In addition, tibial baseplates with a fixed-bearing and a mobile-bearing insert were evaluated to understand differences in the contact properties. The inserts were implanted in neutral alignment and with a 10° internal malrotation. The contact stress, von Mises stress, and equivalent plastic strain (PEEQ) on the tibial posts were extracted for comparison. Results: The stress and strain on the tibial post for the three polyethylenes greatly increased when the insert was placed in malrotation, showing a 38% to 56% increase in von Mises stress and a 335% to 434% increase in PEEQ. The VEPE insert had the lowest PEEQ among the three materials. The mobile-bearing design exhibited a lower increase in stress and strain around the tibial posts than the fixed-bearing design. Conclusion: Using VEPE for the tibial component potentially eliminates the risk of material permanent deformation. The mobile-bearing insert can help to avoid a dramatic increase in plastic strain around the tibial post in cases of malrotation. The mobility allows the pressure to be distributed on the tibial post and demonstrated lower stresses with all three polyethylenes simulated. Cite this article: Bone Joint Res 2020;9(11):768–777.